Antimicrobial therapy in veterinary medicine - Prescott, John F. (Lowa State University Press, 1993)
"Antimicrobial therapy in veterinary medicine" includes coverage of the most recent antimicrobial agents developed for use in human or veterinary medicine. Chapters on regulation, growth promotion uses, and antimicrobial drug residues are fully revised to reflect extensive re-examination in many countries of the use of antimicrobial agents as growth promoters or in the prevention of disease in animals. Veterinarians, specialists, and students alike will find this book to be an indispensable reference on the general principles, special considerations, and clinical applications of virtually all types of antimicrobials used in veterinary medicine.